Forward current-voltage characteristics simulation of 4H-SiC silicon carbide Schottky diode for power electronics - Rybalka, S.B.; Krayushkina, E.Yu.; Demidov, A.A.; Shishkina, O.A.; Surin, B.P. (International Journal of Physical Research, 2017)
Forward current-voltage characteristics of 4H-SiC Schottky diode with Ni Schottky contact have been simulated based on in the physical analytical models based on Poissonâ€™s equation, drift-diffusion and continuity equations. On the base of analysis of current-voltage characteristics in terms of classical thermionic emission theory it is established that the proposed simulation model of Schottky diode corresponds to the â€œidealâ€ diode with average ideality factor nÂ»1.1 at low temperature 300 K. It is determined that effective Schottky barrier height equals 1.1 eV for Ni/4H-SiC Schottky diode.